Karies gigi terhadap balita stunting dan gizi buruk - Alicia Wongkar, Michelle; Asia, Rr. Asyurati; Talenta Theresia, Tiarma (Jurnal Kedokteran Gigi Terpadu, 2024)
Parents' knowledge of the health of toddlers, especially mothers, is very important in sustaining the good growth of toddlers. The mother's knowledge of the nutritional factors and oral health of toddlers is something that must be considered so that when the toddler is in the womb until birth. Insufficient maternal knowledge can have a negative impact on the child's health, disrupting growth such as stunting and malnutrition.